Determinants of Needle-Stick Injuries among Healthcare Workers in Tertiary Health Institutions, Rivers State, Nigeria - , Orisa-Ubi, Charity; , Amadi, Christian Emeka (Archives of Current Research International, 2025)
Healthcare workers in Rivers State’s tertiary health institutions in the course of their daily activities make one error or the other, one of which may be Needle-Stick Injuries (NSI). This study investigated the determinants of needle-stick injuries among healthcare workers in tertiary health institutions, Rivers State. The study adopted descriptive cross sectional survey design with a population of 4,100 healthcare workers in the three functional tertiary health institutions in Rivers state. A sample size of 879 was determined using Cochran formula and a multi-stage sampling procedure. Instrument for data collection was a structured questionnaire titled “Determinants of Needle-Stick Injuries among Healthcare Workers Questionnaire” (DNIHWQ). The instrument has a reliability coefficient of 0.82. Analysis was done using statistical tools such as mean, percentage, frequency, standard deviation and logistic regression at 0.05 level of significance. The result of the study showed that, the extent to which case acuity constituted a determinant to needle-stick injuries was high as the grand mean of 2.70±0.806 was higher than the criterion mean of 2.5. Furthermore, the extent to which safe injection practices constituted a determinant to needle-stick injuries was high as the grand mean of 2.71±0.767 was also higher than the criterion mean of 2.5. There was a significant association between availability of safety devices and needle-stick injuries (F-value = 66.319, df = 1, p-value = 0.000). In conclusion, the determinants of needle-stick injury among healthcare workers in public tertiary health institutions, Rivers State were case acuity, availability of safety devices and safe injection practice. It was recommended among others that, managers of health institutions should provide safety devices like puncture resistant disposal containers, to further reduce the NSI incidents among healthcare workers and healthcare workers should adhere to relevant guidelines & policies for preventive action to reduce the incidence of needle-stick injuries.